Tubercular lymphadenitis - diagnostic evaluation - Datta, PG; Hossain, MD; Amin, SA; Rahman, MK; Das, PP; Saha, KL; Taous, A; Biswas, AK; Datta, A (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 233-7. The abstract of this article is available on the PubMed website